Meningkatkan Daya Saing UMKM Desa Gandasoli: Pendekatan Door-To-Door dalam Penggunaan Pemasaran Digital dan Penyuluhan Legalisasi: Penelitian - Johan Tanaya; Deden Saepudin; Eti Jumiati; Risman Syafarullah; M. Rifki Mulyana; Riski Taufik Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve the competitiveness of MSMEs in Gandasoli Village, Plered District, Purwakarta, through community service based on digital marketing and Islamic financial management. The method used was door-to-door interviews with five MSMEs, followed by socialization of digital marketing, NIB management, halal certification, and Islamic finance. Data were analyzed using NVivo 12 Plus and compared with previous research. The results show that MSMEs face obstacles in understanding digital marketing, sound finance, and business legality, but opportunities are open through training, Islamic financial literacy, and legal assistance. Digital marketing expands the market, while Islamic finance supports business sustainability. This program provides practical solutions for MSMEs in Gandasoli and emphasizes the importance of collaboration between the government, educational institutions, and the community to empower MSMEs in the digital era.